Fiscal decentralization and economic growth in OECD countries: is there a relationship? - Baskaran, Thushyanthan; Feld, Lars P. (CESifo working papers, 2009)
We study the relationship between fiscal decentralization and economic growth for 23 OECD countries from 1975 to 2001 by using new panel data on sub-federal tax autonomy. While initial estimations suggest that fiscal decentralization causes lower growth rates, we find that this result is not robust to alternative specifications. We also fail to obtain evidence for a negative relationship in a number of additional robustness checks. We thus conclude that fiscal decentralization is unrelated to economic growth.
Literaturverz. S.18-19
Keywords: 1975-2001; Geschichte 1975-2001; Wirtschaftswachstum; Fiskalföderalismus; OECD